Network Fragmentation Measure in Elastic Optical Networks - Bonani, L. H.; Forghani-Elahabad, M.; Abbade, M. L.F. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The Elastic Optical Network (EON) with multirate transmission and supported by bandwidth-variable switching technologies has provided more efficient utilization of spectral resources, leading to improvement of the network throughput. However, EON experiences a higher degree of fragmentation than conventional fixed-grid networks because of the spectrum continuity constraint and due to the dynamic nature of setup and release of the connections. In this work we propose and analyze some network fragmentation metrics, one of them applied to evaluate the spectrum fragmentation only due to the contiguity constraint.
Keywords: elastic optical network; network fragmentation; network utilization